Alternative Civic Education and Social Propaganda - Mažeikis, Gintautas (Problemos, 2006)
Development of modern democracy and civic consciousness in the society of spectacle and mass manipulation are the main object of the article. Democratic self government depends both on individual, responsible solutions of citizens and on social, cultural or political propaganda. Propaganda is interpreted as a special, focused persuasion for motivation, consolidation, education purposes. Differences and similarities between social engineering, social propaganda, social marketing and social advertisement are discussed in the paper. Social marketing is interpreted as the response to social needs and the main demands of local people. On the contrary, social propaganda is more didactic, perspective and tries to motivate people for productive activities. Social marketing is more effective in a short period and social propaganda is more useful in a long perspective. Differences between reportage, daily media and propaganda are discussed in the article. Social propaganda needs participatory media. Various forms of participatory media (embedded, engaged and embodied) are analyzed. The topic of social engineering is analyzed on the basis of K. Popper’s considerations. Popper differentiates between utopian or totalitarian engineering and “piecemeal social engineering“. Popper’s conception of utopian engineering is partly criticized. Every big social project is not only a form of elimination of mistakes; it also has utopian features and dream perspectives. The truth of democratic development couldn’t be evaluated only by Popper’s principle of fallibilism. More important are the alternative, competitive forms of social propaganda and open public discussions. The phenomenon and examples of social advertisement are inter preted in the paper. Social advertisement is a necessary part of social propaganda and supports sustainable development and self-government of society. The importance of social advertisement could be compared with other genres of propaganda, such as banners, posters, movies, slogans, etc. Development of modern democracy needs alternative and competitive forms of social propaganda. Propaganda without alternatives is one dimensional persuasion and constructs a subject of manipulation or a subject of propaganda. However, the origin of competitive alternatives needs free public domains, a culture of dialogue, open criticism and experience in protest. Young eastern democracies like in Lithuania tend to destroy public spaces, especially cultural public domains. Different cases and practices of destroying the public spaces are analyzed as the erosion of democracy. On the contrary, public interest and civic consciousness need to defend publicity and to develop critical and dialogue issues of civic society. For these purposes, modern democracy needs to develop alternative civic education. Alternative civic education presupposes education of protest culture, analysis of international and local civic conflicts and protest actions, preparing its manifestations and artificial representations, special projects and civic competitions. Examples of alternative protest laboratories, actions, petitions, manifestations, banners, performances, movies are interpreted in the article.